Quality of Online Learning Participation in a Context of Crisis - Montano-Espinoza, R; Barrera-Capot, R (Walden University, 2021)
Objectives: The COVID-19 pandemic has forced educational institutions to adopt online tools to remotely teach and efficiently use virtual learning situations during the emergency. However, although these environments may serve to improve teaching processes, several issues must be considered to ensure quality student learning. The purpose of our study was to examine types of participation in virtual learning settings by analyzing the level of information contained in message posts and the depth of contributions made by students. Method: We analyzed data from a computer programming module taught online using a learning management system during the first year of a computer science degree program at a Chilean university. We conducted a content analysis of the messages posted in the forums, followed by a statistical analysis of the codified data. For the latter, we used quantitative methods to identify relationships between the level of information contained in student contributions (information level) and a series of covariates, such as message length, perception of achieved learning, final grade, and message depth. Results: Results show that Number of Words (B = 0.02, SE = 0.002), Final Grade (B = 0.45, SE = 0.22), and Student Self-Perceived Learning (B = -0.82, SE = 0.40) predict higher Information Level. Conclusions: A clearer understanding of the relationship between forms of participation in online collaborative environments and the quality of participants contributions would support activities that are conducive to improved participant learning. Implication for Practice: Results revealed the need for guidelines that define online classroom activities, as these have a considerable influence on the generation of dialogue that is conducive to the attainment of new knowledge. © The Author(s)